Impact of Triple Roll Milling Processing Parameters on Fluidic/Rheological and Electrical Properties of Aqueous Graphene Ink. Issue 4 (9th January 2020) - Kumar, Sandeep; Kumar, Pramod; Bhatt, Kapil; Shrivastva, Shilpi; Kumar, Amit; Singh, Ravinder; Punia, Rajesh; Tripathi, Chandra Charu
Abstract : Graphene ink is a potential candidate for the printing of electronic devices. Rheological studies of graphene inks are necessary to estimate and tune the behavior of ink during and after printing. Ink constituents and their fundamental properties play an important role in modifying the rheological behavior of ink. During the processing of ink, modification of these properties takes place. So, it is quite important to investigate the role of processing equipment on the ink constituents and correspondingly on the rheological behavior of ink and printed functional devices. Herein, graphene ink formulation through a triple roll mill (TRM) is presented. The particle size of graphene ink reduces substantially with both the speed of rollers and number of passes. Approximately 52% reduction in particle size is observed after five passes at the highest roller speed, and it further reduces up to 72% with an increase in the number of passes. Correspondingly, solvent loss, density, and viscosity of the inks are observed in respect of roller speed and number of passes. The impact of TRM parameters on ink constituents, rheology, and electrical properties of screen‐printed resistors is discussed and explained in terms of simple analytical models. Abstract : Herein, the impact of triple roll mill processing parameters is shown on graphene ink particle size and correspondingly variation in the electrical resistance of screen‐printed resistors is presented.